A new user interface for ADiMat: toward accurate and efficient derivatives of MATLAB programmes with ease of use. (1st January 2014) - Willkomm, Johannes; Bischof, Christian H.; Bücker, H. Martin
Various techniques in computational science and engineering benefit from accurate and efficient derivative computation. ADiMat is a software tool that transforms a numerical program written in MATLAB into another MATLAB programme for the computation of derivatives that are free from truncation error. We introduce a new and easy-to-use interface for ADiMat and present case studies from geophysics and fluid mechanics to quantify the performance of the code generated by ADiMat.